The invention of northern aesthetics in 18th-century English literature - Bezrucka, Yvonne (Cambridge Scholars Publishing, 2017)
Free, romantic, and individualistic, Britain's self-image in the eighteenth century constructs itself in opposition to the dominant power of a southern European aesthetics. Offering a fresh understanding of how the British intelligentsia created a 'Northern' aesthetics to challenge the European yoke, this book explores the roots of British Romanticism and a newly created past. Literature, the arts, architecture, and gardening all contributed to the creation of this national, 'enlightened', Northern cultural environment, with its emphasis on a home-grown legal tradition, on a heroic Celtic past.